Līlārasataraṅgiṇī - Śivaprakāśa Siṃha, 1787-1847 (Bihāra-Rāshṭrabhāshā-Parishad, 1982)
Extended narrative poem on the life and exploits of Rāma, Hindu deity; critical edition, with elaborate introduction.